Understanding one health and zoonosis: a systematic review with a bibliometric analysis of turkish research and global perspectives (1974-2023) - Samba Deguene DIOP; Abdullah INCI; Alina Denis KIZGIN; Onder DUZLU (Kafkas Universitesi Veteriner Fakültesi Dergisi, 2025)
A bibliometric analysis explored the understanding of the "One Health" and "zoonosis" concepts among Turkish researchers and identified existing gaps. The analysis examined trends in research on "One Health," "zoonosis," and "zoonoses," focusing on publications from Türkiye and globally. Data from Scopus were analyzed using VOSviewer and RStudio software. The results showed that research interest in these concepts has grown in Türkiye since the 2000s. However, the number of articles from Türkiye remains low compared to developed countries. The interdisciplinary nature of "One Health" and "zoonosis" research in Türkiye reflects contributions from various academic fields. Medical sciences lead in research, followed by immunology and veterinary sciences. In Türkiye, "One Health" is predominantly associated with animals, especially felines, and zoonotic pathogens such as Toxoplasma, Anthrax, and Echinococcus. It also relates to epidemiology, infectious diseases, and antibiotic resistance. Globally, "One Health" has a broader perspective, encompassing environmental health, education, veterinary medicine, and food safety. Regarding "zoonosis," Türkiye focuses on pathogens such as Anthrax, Echinococcus, Brucella, Leishmania, and Hantavirus. Globally, additional pathogens such as Rickettsia, Taenia solium, and Giardia are included. "Zoonosis" is also linked to climate change, animal welfare, and vector- and food-borne diseases. Despite increased interest, Türkiye"s scientific production remains limited. Emphasis on interdisciplinary collaboration and broader conceptual frameworks could enhance understanding and research impact.